Trilaciclib prior to chemotherapy and atezolizumab in patients with newly diagnosed extensive‐stage small cell lung cancer: A multicentre, randomised, double‐blind, placebo‐controlled Phase II trial. Issue 10 (12th January 2021) - Daniel, Davey; Kuchava, Vladimer; Bondarenko, Igor; Ivashchuk, Oleksandr; Reddy, Sreekanth; Jaal, Jana; Kudaba, Iveta; Hart, Lowell; Matitashvili, Amiran; Pritchett, Yili; Morris, Shannon R.; Sorrentino, Jessica A.; et al.
Abstract: Trilaciclib is an intravenous CDK4/6 inhibitor administered prior to chemotherapy to preserve haematopoietic stem and progenitor cells and immune system function from chemotherapy‐induced damage (myelopreservation). The effects of administering trilaciclib prior to carboplatin, etoposide and atezolizumab (E/P/A) were evaluated in a randomised, double‐blind, placebo‐controlled Phase II study in patients with newly diagnosed extensive‐stage small cell lung cancer (ES‐SCLC) (NCT03041311). The primary endpoints were duration of severe neutropenia (SN; defined as absolute neutrophil count <0.5 × 10 9 cells per L) in Cycle 1 and occurrence of SN during the treatment period. Other endpoints were prespecified to assess the effects of trilaciclib on additional measures of myelopreservation, patient‐reported outcomes, antitumour efficacy and safety. Fifty‐two patients received trilaciclib prior to E/P/A and 53 patients received placebo. Compared to placebo, administration of trilaciclib resulted in statistically significant decreases in the mean duration of SN in Cycle 1 (0 vs 4 days; P < .0001) and occurrence of SN (1.9% vs 49.1%; P < .0001), with additional improvements in red blood cell and platelet measures and health‐related quality of life (HRQoL). Trilaciclib was well tolerated, with fewer grade ≥3 adverse events compared with placebo, primarily due to less high‐grade haematological toxicity. Antitumour efficacy outcomes were comparable. Administration of trilaciclib vs placebo generated more newly expanded peripheral T‐cell clones ( P = .019), with significantly greater expansion among patients with an antitumour response to E/P/A ( P = .002). Compared with placebo, trilaciclib administered prior to E/P/A improved patients' experience of receiving treatment for ES‐SCLC, as shown by reduced myelosuppression, and improved HRQoL and safety profiles.